Energy Harvesting on Pavement: A Review - A. F., Ahmad; A. R., Razali; F. R. M., Romlay; I. S. M., Razelan (ijrer.org, 2021)
Rapid urbanization has increased the Malaysian economy’s dependence on imports of fossil fuels such as oil, petroleum, and natural gas for energy output. Excessive use of fossil fuels contributes to high greenhouse gas emissions and this causes climate change and affects the ecological balance. Therefore, energy generation through harvesting technology is much needed to improve the ecological balance. The process for energy harvesting begins with capturing and accumulating the wasted energy then storing it to be used later. According to a study conducted by the World Economic Forum, roads in Malaysia are among the best in the world on par with Korea and better than some of the European countries. Malaysia’s road network that connects the states, districts, and villages are also growing every year for the convenience of the people. Good road structure throughout Malaysia can give benefit the country by using it as an energy source. The energy sources that can be exploited from the pavement are solar radiation, mechanical energy generated from moving vehicles or pedestrians, and geothermal energy. This paper analyzes key issues in pavement energy harvesting and proposing the best energy harvesting technique for Malaysia climate. The keys issues were addressed accordingly and gaps that existed in the field were presented. The outcomes of the review are brief in a concise manner.